1959
DOI: 10.1152/ajplegacy.1959.197.5.943
|View full text |Cite
|
Sign up to set email alerts
|

Role of the non-Newtonian behavior of blood in hemodynamics

Abstract: The role of the non-Newtonian behavior of blood in perfused vascular beds has been assessed by measuring the pressure-flow curves of erythrocyte suspensions with hematocrits from 9 to 85%, in glass tubes of radii from 50 to 800 µ. The curves become linear as the flow increases, and for each tube, point back to a ‘nodal point’ on the negative flow axis which is independent of hematocrit. From this data, curves of the rate of shear versus shearing stress at the wall (consistency curves) were obtained which are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
1
1

Year Published

1962
1962
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(55 citation statements)
references
References 0 publications
3
50
1
1
Order By: Relevance
“…The asymptotic lines (extrapolated linear segments) of P-Q curves in a glass tube converge to the same point on the negative 0-axis (Fig. 3A), and similar results have been reported in the perfusion of a glass tube (HAYNES and BURTON, 1959) and in the perfusion of a bullfrog's hind limb (INOUYE et al, 1976). On the other hand, the asymptotic lines of P-Q curves in NP membrane do not meet at a single point on the negative Q-axis (Figs.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The asymptotic lines (extrapolated linear segments) of P-Q curves in a glass tube converge to the same point on the negative 0-axis (Fig. 3A), and similar results have been reported in the perfusion of a glass tube (HAYNES and BURTON, 1959) and in the perfusion of a bullfrog's hind limb (INOUYE et al, 1976). On the other hand, the asymptotic lines of P-Q curves in NP membrane do not meet at a single point on the negative Q-axis (Figs.…”
Section: Discussionsupporting
confidence: 86%
“…3A). It can be concluded that the increase in the value of the negative intercept in the perfusion of NP membrane indicates clearly an obstruction or plugging of the pores by erythrocytes, taking theoretical and experimental results in the perfusion of a rigid glass tube (GORDON,1970;HAYNES and BURTON, 1959) and of a bullfrog's hind limb (INOUYE et al, 1976) into account. It is suggested also that the non-linear part of the P-Q relationships of erythrocyte suspensions in the perfusion of NP membrane is due mainly to non-Newtonian properties of suspension and partly to the obstructive procedure of erythrocytes during passage through a membrane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have demonstrated that the rheological properties of blood are anomalous, in particular, that rate of flow through cylindrical tubing is not related linearly to the imposed gradient in pressure and that the viscosity of blood increases at low rates of flow (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). These data, and similar data obtained by means of other viscometric methods (11)(12)(13), are characteristic of non-Newtonian flow (14) and necessitate that any study of the rheological properties of blood must examine the dependence of viscosity upon applied shearing stress.…”
mentioning
confidence: 99%